PANDANGAN FILSAFAT PERENNIAL TERHADAP KRISIS SPRITUAL MANUSIA MODERN - Putu Maria Ratih Anggraini; Gde Mahardika (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Perennial philosophy is a point of view in the philosophy of religion which believes that every religion in the world has a single and universal truth which is the basis of all religious knowledge and doctrine. Perennial philosophy is now one of the important philosophies, in order to understand the complexity of religions and their involvement in various humanitarian issues today, such as the crisis of spirituality due to all-out pressure of modernism, environmental crises, the desire to provide theoretical basis for religious plurality. the source of religious ethics can never be predicted for its meaning only through empirical, especially historical analysis, as was done by historians of religions so far, who interpret religion in a framework of suspicion of the interpretation of exercise of suspicion unless we want to make a reductionism run out - devotion to religion, which would certainly be rejected by believers. That is why a religious metaphysical framework is still needed, not only for a theological conceptualization, but more so for an ethical search with religions.